2017
DOI: 10.1038/nn.4645
|View full text |Cite
|
Sign up to set email alerts
|

A pathway from midcingulate cortex to posterior insula gates nociceptive hypersensitivity

Abstract: The identity of cortical circuits mediating nociception and pain is largely unclear. The cingulate cortex is consistently activated during pain, but the functional specificity of cingulate divisions, the roles at distinct temporal phases of central plasticity and the underlying circuitry are unknown. Here we show in mice that the midcingulate division of the cingulate cortex (MCC) does not mediate acute pain sensation and pain affect, but gates sensory hypersensitivity by acting in a wide cortical and subcorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 53 publications
4
111
0
4
Order By: Relevance
“…Unless otherwise stated, pain-related behavioral tests were performed at day 1, 3, 5, and 7 after the CFA injection. For neuropathic pain, we adopted a well-established spared nerve injury (SNI) model as previously described (Bourquin et al, 2006;Chen et al, 2015;Tan et al, 2017). Briefly, the mice were anesthetized with isoflurane, and an incision was made to the lateral skin surface of the thigh to expose the sciatic nerve and its branches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise stated, pain-related behavioral tests were performed at day 1, 3, 5, and 7 after the CFA injection. For neuropathic pain, we adopted a well-established spared nerve injury (SNI) model as previously described (Bourquin et al, 2006;Chen et al, 2015;Tan et al, 2017). Briefly, the mice were anesthetized with isoflurane, and an incision was made to the lateral skin surface of the thigh to expose the sciatic nerve and its branches.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we tested whether ASIC1a antagonism has similar antihyperalgesic effects in other animal models of chronic pain. We used the well-established SNI model of neuropathic pain in adult mice as previously described (Bourquin et al, 2006;Tan et al, 2017). Post-treatment with intra-ACC administration of PcTx1 at 7 d after SNI significantly reversed the mechanical allodynia, with the analgesic effect lasting for at least 90 min (F (1,9) ϭ 26.94, p ϭ 0.0006, two-way repeated-measures ANOVA; Tukey's multiple-comparison test: saline vs PcTx1, p ϭ 0.0004, p Ͻ 0.0001, and p ϭ 0.0074 for 10, 30, and 90 min, respectively; Fig.…”
Section: Blocking Asic1a In Acc Reverses Established Pain Hypersensitmentioning
confidence: 99%
“…Multiple changes are observed in the pain matrix that includes the medial prefrontal cortex, nucleus accumbens, anterior cingulate cortex, insula, amygdala, periaqueductal gray, locus coeruleus, and rostroventral medulla (Schweinhardt and Bushnell, 2010;von Hehn et al, 2012;Zhang et al, 2015c;Peirs and Seal, 2016;Tan et al, 2017;Taylor et al, 2017). For example, synapses in the anterior cingulate cortex are altered after peripheral nerve injury, and LTP of glutamatergic transmission appears in the insula (Zhuo, 2016a).…”
Section: F the Pain Matrixmentioning
confidence: 99%
“…Rodent studies further demonstrated roles for the IC in multisensory (Gogolla, Takesian, Feng, Fagiolini, & Hensch, 2014; Rodgers, Benison, Klein, & Barth, 2008) and pain processing (Tan et al, 2017), representation of valence (Wang et al, 2018), learning and memory (Bermúdez-Rattoni, Okuda, Roozendaal, & McGaugh, 2005; Lavi, Jacobson, Rosenblum, & Lüthi, 2018), social interactions (Rogers-Carter et al, 2018), gustation (Peng et al, 2015; Wang et al, 2018), drug cravings and malaise (Contreras, Ceric, & Torrealba, 2007), and aversive states such as hunger, thirst, and anxiety (Gehrlach et al, 2019; Livneh et al, 2017, 2020).…”
Section: Introductionmentioning
confidence: 99%